2017
DOI: 10.1111/brv.12354
|View full text |Cite
|
Sign up to set email alerts
|

Understanding processes at the origin of species flocks with a focus on the marineAntarctic fauna

Abstract: Species flocks (SFs) fascinate evolutionary biologists who wonder whether such striking diversification can be driven by normal evolutionary processes. Multiple definitions of SFs have hindered the study of their origins. Previous studies identified a monophyletic taxon as a SF if it displays high speciosity in an area in which it is endemic (criterion 1), high ecological diversity among species (criterion 2), and if it dominates the habitat in terms of biomass (criterion 3); we used these criteria in our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 157 publications
(250 reference statements)
2
19
0
Order By: Relevance
“…Front account for about 10% of all known echinoid species reported worldwide (Saucède et al, 2014) (Saucède et al, 2014); a similar pattern was also found in other marine groups (Chenuil et al, 2018;Clarke, 2008;Lecointre et al, 2013;Saucède et al, 2014). The speciose families Cidaridae and Schizasteridae in the Antarctic (Poulin & Féral, 1996), which represent about 65% of all Antarctic echinoid species, are also highly endemic to the Antarctic continental shelf with 81% and 67% of endemic species, respectively (David et al, 2005;Pearse, Mooi, Lockhart, & Brandt, 2009;Pierrat et al, 2012;Saucède et al, 2014).…”
Section: In Total Antarctic Echinoid Species Distributed South Of Thmentioning
confidence: 54%
See 1 more Smart Citation
“…Front account for about 10% of all known echinoid species reported worldwide (Saucède et al, 2014) (Saucède et al, 2014); a similar pattern was also found in other marine groups (Chenuil et al, 2018;Clarke, 2008;Lecointre et al, 2013;Saucède et al, 2014). The speciose families Cidaridae and Schizasteridae in the Antarctic (Poulin & Féral, 1996), which represent about 65% of all Antarctic echinoid species, are also highly endemic to the Antarctic continental shelf with 81% and 67% of endemic species, respectively (David et al, 2005;Pearse, Mooi, Lockhart, & Brandt, 2009;Pierrat et al, 2012;Saucède et al, 2014).…”
Section: In Total Antarctic Echinoid Species Distributed South Of Thmentioning
confidence: 54%
“…The speciose families Cidaridae and Schizasteridae in the Antarctic (Poulin & Féral, 1996), which represent about 65% of all Antarctic echinoid species, are also highly endemic to the Antarctic continental shelf with 81% and 67% of endemic species, respectively (David et al, 2005;Pearse, Mooi, Lockhart, & Brandt, 2009;Pierrat et al, 2012;Saucède et al, 2014). This high level of endemicity and the prevalence of a taxonomically limited number of speciose groups were found in many other marine groups in the Antarctic, and particularly on the continental shelf where species flocks were identified (Chenuil et al, 2018;Clarke & Crame, 2010;Eastman, 2000;Lecointre et al, 2013). Endemicity is even more pronounced in the less-extended sub- (David et al, 2005;Fabri-Ruiz et al, 2018;Guillaumot et al, 2018;Saucède et al, 2014).…”
Section: In Total Antarctic Echinoid Species Distributed South Of Thmentioning
confidence: 92%
“…Molecular phylogenetic evidence also suggests that the amphipod genus Epimeria , which forms a species flock at the present day in the Southern Ocean, can be traced back to an initial Middle or Late Eocene Antarctic radiation (Verheye, Backeljau, & d'Udetem d'Acoz, ). There is a particularly strong pulse of diversification immediately after the MMCT (Chenuil et al., ; Verheye et al., ).…”
Section: An Outline Of the Key Stagesmentioning
confidence: 99%
“…In addition to extrinsic environmental factors, intrinsic factors (such as dispersal ability, genetic architecture or chromosomal instability; see [3]) specific to Patagonotothen might have played a role in the diversification of this clade. This is suggested, for example, by their comparison with the evolutionary history of Eleginops maclovinus , another notothenioid species occurring along the Patagonian coast.…”
Section: Introductionmentioning
confidence: 99%